A parametric study on thermal performance of microchannel heat sinks with internally vertical bifurcations in laminar liquid flow. (February 2018) - Shen, Han; Wang, Chi-Chuan; Xie, Gongnan
Highlights: Microchannel heat sinks with large space interval distances are studied. Eight kinds of microchannels with internal vertical bifurcation are designed to find out the optimal position. Thermal characteristics on bottom surfaces of microchannels are described in detail. Convective flow and pressure drop characteristics are investigated. Abstract: The optimal position of internal vertical bifurcation integrated with a microchannel heat sink (MHS) is investigated numerically in the present research. The corresponding rectangular smooth microchannel is compared with those with internal vertical bifurcation. The optimal position along the streamwise direction for interval distances is studied in detail. The corresponding temperature fields, flow fields, pressure drop and thermal characteristics are presented through verified computational model. The numerical simulation indicates that a clear inflection point of pressure gradient may prevail with the presence of internal vertical bifurcation. It is also found that the microchannel heat sink with a small distance between the tail end of internal vertical bifurcation and the outlet of microchannel shows the best thermal performance instead of those with setting the tail end of internal bifurcation at the outlet of microchannel. The proposed optimal design of internal vertical bifurcation shows improved thermal performance without any pressure drop penalty.